Effectiveness of Quality Incentive Payments in General Practice (EQuIP-GP) cluster randomized trial: impact on patient-reported experience. (23rd November 2021) - Bonney, Andrew; Russell, Grant; Radford, Jan; Zwar, Nicholas; Mullan, Judy; Batterham, Marijka; Mazza, Danielle; Peterson, Gregory; Eckermann, Simon; Metusela, Christine
Abstract: Background: Relational continuity, 'a therapeutic relationship between a patient and provider/s that spans health care events', has been associated with improved patient outcomes. Objectives: To evaluate whether an intervention incorporating patient enrolment and a funding model for higher-risk patients influenced patient-reported experience measures, particularly relational continuity. Methods: Cluster-randomized controlled trial over 12 months (1 August 2018–31 July 2019). Participating patients within intervention practices were offered enrolment with a preferred general practitioner, a minimum of 3 longer appointments, and review within 7 days of hospital admission or emergency department attendance. Intervention practices received incentives for longer consultations (dependent on reducing unnecessary prescriptions and tests), early post-hospital follow-up, and hospitalization reductions. The primary outcome was patient-reported relational continuity, measured by the Primary Care Assessment Tool Short Form. Results: A total of 774 patients, aged 18–65 years with a chronic illness or aged over 65 years, from 34 general practices in metropolitan, regional, and rural Australia across 3 states participated. Response rates for questionnaires were >90%. From a maximum of 4.0, mean baseline scores for relational continuity were 3.38 (SE 0.05) and 3.42 (SE 0.05) in control and intervention arms, respectively, with no significant between-group differences in changes pre-post trial. There were no significant changes in other patient-focussed measures. Conclusion: Patient-reported relational continuity was high at baseline and not influenced by the intervention, signalling the need for caution with policies incorporating patient enrolment and financial incentives. Further research is required targeting at-risk patient groups with low baseline engagement with primary care. Lay Summary: Relational continuity, 'a therapeutic relationship between a patient and provider/s that spans health care events', has been associated with improved patient outcomes. This study aimed to evaluate whether patient enrolment with a preferred general practitioner (GP) and a funding model for higher-risk patients influenced patient-reported experience measures, particularly relational continuity. The trial was randomized by practice and ran over 12 months (1 August 2018–31 July 2019). Participating patients within intervention practices were offered enrolment with a preferred GP, a minimum of 3 longer appointments, and review within 7 days of hospital discharge. Intervention practices received incentives for longer consultations (with quality improvements), early post-hospital follow-up, and hospitalization reductions. We measured patient experience using the Primary Care Assessment Tool—Short Form at baseline and completion. A total of 774 patients, aged 18–65 years with a chronic illness or aged over 65 years, from 34 general practices in metropolitan, regional, and rural Australia participated. Patient-reported relational continuity was high at baseline and not influenced by the intervention. There were no significant changes in other patient-focussed measures. We advise caution with policies incorporating patient enrolment and financial incentives. Further research is required targeting at-risk patient groups with low baseline engagement with primary care.